1978
DOI: 10.1071/bi9780363
|View full text |Cite
|
Sign up to set email alerts
|

a-Glucosidase Activity in the Reproductive Tract of the Ewe

Abstract: Aust. J. Bioi. Sci., 1978, 31, 363-71 ex-Glucosidase-activity has been estimated in the tissues and rinsings of the reproductive tract of the ewe. There were peaks of activity in the oviducal mucosa at pH 4·0 and 5·7. In the endometrium, caruncles and cervical mucosa the pH optimum occurred from pH 4·0 to pH 5·7. A sharp peak in the activity in the vaginal mucosa occurred at pH 5 ·7.The only tissue in which changes in enzyme activity were consistently related to one endocrinological state of the ewe was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In this tissue IX-amylase and glycogen phosphorylase remained constant, but the activity of acid lX-l,4-g1ucosidase was at a maximum at day 0 in the cervical mucosa (O'Shea and Murdoch 1978b). Thus in the oviduct and cervix both synthesis and degradation of glycogen are increased at oestrus.…”
Section: Discussionmentioning
confidence: 75%
“…In this tissue IX-amylase and glycogen phosphorylase remained constant, but the activity of acid lX-l,4-g1ucosidase was at a maximum at day 0 in the cervical mucosa (O'Shea and Murdoch 1978b). Thus in the oviduct and cervix both synthesis and degradation of glycogen are increased at oestrus.…”
Section: Discussionmentioning
confidence: 75%
“…A study in ewes determined that GAA activity did not change through the oestrous cycle (O'Shea & Murdoch, 1978). In agreement, we found that the activity of GAA did not increase in BUTE cells treated with progesterone.…”
Section: Discussionmentioning
confidence: 99%